Forward Guidance for Monetary Policy: Is It Desirable? - Hans Gersbach; Volker Hahn (ETH Zurich, CER-ETH - Center of Economic Research, 2008)
In this paper we assess whether forward guidance for monetary policy regarding the future path of interest rates is desirable. We distinguish between two cases where forward guidance for monetary policy may be helpful. First, forward guidance may reveal private information of the central bank. We argue that vague, non-binding statements may be desirable. Second, forward guidance may be used as a commitment device. In this case, policy forecasts may be desirable in a classic inflation-bias framework but not in a New Keynesian framework.
Keywords: E58; D70; 330; central banks; transparency; commitment; Federal Reserve; policy inclinations; signaling; Geldpolitisches Ziel; Zinspolitik; Politische Kommunikation; Signalling; Neoklassische Synthese; Theorie